The Urgency of Establishing Special Regulations Regarding the Promotion and Advertising of Dental Services Based on Ethics and Consumer Protection - Sarwono, Aditya Pratama; Santiago, Faisal (Greenation Publisher & Yayasan Global Resarch National, 2025)
Promotion and advertising of dental services are increasingly common, especially through digital media, but have not been balanced with specific and adequate legal regulations. Currently, regulations regarding advertising of dental services are still general and spread across various regulations, such as the Medical Practice Act, the Consumer Protection Act, and professional codes of ethics. The absence of specific regulations that specifically regulate the limitations, forms, and supervision of dental promotions raises the potential for ethical violations, medical misinformation, and consumer losses. This study aims to analyze the urgency of establishing specific regulations that can comprehensively regulate the advertising of dental services by considering legal aspects, professional ethics, and consumer protection. The method used is a normative legal approach with an analysis of laws and regulations, literature studies, and comparisons of practices in several other countries. The study results indicate that the legal vacuum in regulating dental advertising can cause legal uncertainty and reduce public trust in the dental profession. Therefore, regulations that are firm, adaptive to technological developments, and in line with the principles of medical ethics are needed.